Dampak Perceraian Terhadap Kesejahteraan Ekonomi Keluarga pada Masa Pandemi Covid 19 di Kota Tegal - Bahri Kamal; Anita Karunia; Ghea Dwi Rahmadiane (Concept: Journal of Social Humanities and Education, 2024)
This study aims to determine the Impact of Divorce on Family Economic Welfare During the Covid 19 Pandemic In Tegal City. The sampling technique used was convenience or random sampling, namely by looking at respondents who were willing to be interviewed depending entirely on the convenience of the researcher (Sekaran, 2011). Data collection techniques using observation, interviews, and literature study. The method of data analysis was qualitative using descriptive analysis used to describe how the work profile of the widow, the number of widows' debts, the level of education of the children, and the widow's efforts to maintain her economy for the needs of the family's life by going through the stages of data collection, data reduction, data presentation, draw conclusions and verify. The impact of divorce on the family economy is very much felt especially during the COVID-19 pandemic, where they have to be responsible to their families to replace the husband's role as the head of the household, do the work a man does, not only work to earn a living but they have to educate and care for them. his children. The steps they take to meet the needs of their family after a divorce, there are many ways they do, for example, side work or any work to make money to meet their needs.